2009
DOI: 10.1128/aem.01864-08
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Lanthionines Renders the Lantibiotic Nisin Inactive

Abstract: The peptide antibiotic nisin A belongs to the group of antibiotics called lantibiotics. They are classified as lantibiotics because they contain the structural group lanthionine. Lanthionines are composed of a single sulfur atom that is linked to the ␤-carbons of two alanine moieties. These sulfur atoms are vulnerable to environmental oxidation. A mild oxidation reaction was performed on nisin A to determine the relative effects it would have on bioactivity. High-mass-accuracy Fourier transform ion cyclotron r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 36 publications
0
43
0
1
Order By: Relevance
“…Additionally, many lantibiotics are not stable over the full pH range, as under basic conditions, many peptides undergo oxidation of the lan/ melan thioethers, resulting in a loss of antimicrobial activity. 10 These structural disadvantages along with a desire for smaller/simpler peptides have driven much of the research into lantibiotic analogs. If clinically useful peptides are to be developed from lantibiotics, solutions need to be found for these inherent challenges.…”
Section: Lantibioticsmentioning
confidence: 99%
“…Additionally, many lantibiotics are not stable over the full pH range, as under basic conditions, many peptides undergo oxidation of the lan/ melan thioethers, resulting in a loss of antimicrobial activity. 10 These structural disadvantages along with a desire for smaller/simpler peptides have driven much of the research into lantibiotic analogs. If clinically useful peptides are to be developed from lantibiotics, solutions need to be found for these inherent challenges.…”
Section: Lantibioticsmentioning
confidence: 99%
“…Resistance to hydrolysis may also be, in part, a reflection of the unusual, horseshoe-shaped three-dimensional structure of mutacin 1140 (20,21). The hinge region contains a potentially protease-susceptible arginine at residue 13. This residue appears to be protected, as evidenced by the relative difficulty of inactivating mutacin 1140 by trypsin or pronase treatment (20)(21)(22).…”
mentioning
confidence: 99%
“…Nisin, one of the most studied lanthipeptides, is produced by Lactococcus lactis and has been used in the food industry for over 50 years. It was discovered that both nisin and mutacin 1140 abduct lipid II from the site of new cell wall synthesis, ultimately causing cell death (10)(11)(12)(13). Rings A and B provide the structural motif for binding to lipid II and are referred to as the lipid II binding domain (14).…”
mentioning
confidence: 99%
“…membranes). Wilson-Stanford et al [30] found that oxidation of lantibiotics such as nisin A disrupted antibacterial activity. It was proposed that the oxidized form of sulfur is unable to bind to lipid II of the cell wall.…”
Section: Oxidationmentioning
confidence: 99%
“…While terminal capping, selective D-amino acid incorporation, disulfide bond formation, and head-to-tail cyclization have been applied to rational design of therapeutic peptides, other modifications such as phosphorylation and glycosylation are probably created mainly for specific functional roles of polypeptides only (Table 1). Some type of chemical modifications such as oxidation during peptide storage, however, should be avoided, since it could reduce peptide activity [29,30].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%